Illusion Town - Castle, Jayne; Krentz, Jayne Ann (New York Jove Books, 2016)
"Hannah West isnt the first woman to wake up in Illusion Town married to a man she barely knows, but she has no memory of the ceremony at all. For that matter, neither does Elias Coppersmith, her new husband. All either can remember is that they were on the run. With Hannahs dubious background and shaky para-psych profile, she could have done much worse. The cooly competent mining heir arouses her curiosity--as well as other parts of her mind and body"--Page 4 of cover.
Keywords: Spouses -- Fiction; Inheritance and succession -- Fiction; Sexual attraction -- Fiction; Romantic suspense fiction; Science fiction; Paranormal fiction